The Position of EGF Deprivation in the Management of Advanced Non-Small Cell Lung Cancer - Crombet Ramos, Tania; Santos Morales, Orestes; Dy, Grace K.; León Monzón, Kalet; Lage Dávila, Agustín (Frontiers in Oncology, 2021)
Advanced non-small cell lung cancer (NSCLC) has faced a therapeutic revolution with the advent of tyrosine kinase inhibitors (TKIs) and immune checkpoints inhibitors (ICIs) approved for first and subsequent therapy. CIMAvax-EGF is a chemical conjugate between human-recombinant EGF and P64, a recombinant protein from Neisseria Meningitides, which induces neutralizing antibodies against EGF. In the last 15 years, it has been extensively evaluated in advanced NSCLC patients. CIMAvax-EGF is safe, even after extended use, and able to keep EGF serum concentration below detectable levels. In a randomized phase III study, CIMAvax-EGF increased median overall survival of advanced NSCLC patients with at least stable disease after front-line chemotherapy. Patients bearing squamous-cell or adenocarcinomas and serum EGF concentration above 870 pg/ml had better survival compared to control patients treated with best supportive care as maintenance, confirming tumors’ sensitivity to the EGF depletion. This manuscript reviews the state of the art of NSCLC therapy and proposes the most promising scenarios for evaluating CIMAvax-EGF, particularly in combination with TKIs or ICIs. We hypothesize that the optimal combination of CIMAvax-EGF with established therapies can further contribute to transform advanced cancer into a manageable chronic disease, compatible with years of good quality of life.